THE EFFECT OF USING INSIDE OUTSIDE CIRCLE TECHNIQUE IN TEACHING SPEAKING AT THE GRADE VIII OF SMP NEGERI 1 ANGKOLA TIMUR - Abdul Rahman Siagian (Linguistik : Jurnal Bahasa dan Sastra, 2020)
The study was conducted at the Grade VIII of SMP Negeri 11 Padangsidimpuan. The aims of this research is to find out if there is a significant Effect of Using inside outside circle technique in teaching speaking at the Grade VIII of SMP Negeri 1 Angkola Timur. In order to achieve the purpose of this research, the writer carried out in quantitative approach by applying experimental method. The population of this research was the Grade VIII of SMP Negeri 1 Angkola Timur. They were 155 students, the writer used cluster sampling technique to get the sample. The samples were 36 students. The speaking ability was applied as the instrument of this research, the writer used “t” tes formula. Based on the data that has been analyzed, it can be found that (1) the students’ achievement in speaking ability without using inside outside circle technique was “enough”, (2) their value by using inside outside circle technique can be categorized “good”, and (3) there was a significant effect the result of using inside outside circle technique in teaching speaking at the grade VIII of SMP Negeri 1 Angkola Timur. It meant that the hypothesis was accepted.